Implementasi Penelitian Kemasyarakatan sebagai Pertimbangan Putusan Hakim dalam Perkara Anak yang Berkonflik Dengan Hukum - Salsabella, Karina Farah; Tajuddin, Mulyadi Alrianto; Y. Badilla , Nurul Widhanita (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2025)
Community research is an instrument in the juvenile justice system used to provide a comprehensive overview of the social, psychological, and family conditions of children involved in criminal acts. This study examines the extent to which community research results influence judges' decisions in imposing sanctions or rehabilitation on children in conflict with the law. This research was conducted using an empirical juridical method that examines approaches to legal studies and phenomena occurring in Merauke Regency. The data obtained were then processed into primary and secondary data. The results indicate that although community research provides invaluable information in determining more rehabilitative decisions, there are challenges in terms of limited time and available resources, which can affect the quality of the research results. This study recommends improvements in the process of implementing community research and increasing the time allotted to obtain more accurate results that are appropriate to the needs of children. Furthermore, the study emphasizes that decisions made by judges can provide better recovery and rehabilitation for children